American visceral leishmaniasis dissociated from Lutzomyia longipalpis (Diptera, Psychodidae) in the State of Espírito Santo, Brazil Leishmaniose visceral americana dissociada da presença de Lutzomyia longipalpis (Diptera, Psychodidae) no Estado do Espírito Santo, Brasil - Israel de Souza Pinto; Claudiney Biral dos Santos; Gabriel Grimaldi Jr; Adelson Luiz Ferreira; Aloísio Falqueto (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The occurrence of American visceral leishmaniasis in the State of Espírito Santo, Brazil has always been associated with the presence of the Lutzomyia longipalpis vector. The geographic distribution of this vector in this state is related to the presence of specific geoclimatic characteristics, such as a dry climate, low elevations (< 450m), steep slopes and rocky outcrops. The occurrence of human autochthonous cases of American visceral leishmaniasis in municipalities without these geoclimatic characteristics justifies the present study and our main goal was to test the association between the occurrence of American visceral leishmaniasis and the presence of the Lu. longipalpis. Sand flies were captured monthly from July 2006 to August 2007 using Shannon and CDC traps in two municipalities with records of autochthonous American visceral leishmaniasis and one with no record. We captured 13,112 sand flies, but no Lu. longipalpis was found. The absence of Lu. longipalpis and the possible role of another American visceral leishmaniasis vector in these localities were discussed. A ocorrência de leishmaniose visceral americana no Estado do Espírito Santo, Brasil, sempre foi associada à presença do vetor Lutzomyia longipalpis. A distribuição geográfica desse vetor no estado está relacionada à ocorrência de características geoclimáticas específicas, tais como clima seco, baixas altitudes, relevo acidentado e afloramentos rochosos A ocorrência de casos humanos autóctones de leishmaniose visceral americana em municípios sem essas características geoclimáticas justificou o presente estudo, com objetivo de testar a associação entre a ocorrência de leishmaniose visceral americana e a presença de Lu. longipalpis. Flebotomíneos foram capturados mensalmente de julho de 2006 a agosto de 2007 com uso de armadilhas de Shannon e CDC em dois municípios com registros de leishmaniose visceral americana autóctone e um sem registros. Foram capturados 13.112 flebotomíneos, mas nenhum Lu. longipalpis foi encontrado. A ausência de Lu. longipalpis e a possível participação de outro vetor de leishmaniose visceral americana nessas localidades foram discutidas.